Patients’ experiences after CKD diagnosis: a meta-ethnographic study and systematic review - Teasdale, E; Leydon, G; Fraser, S; Roderick, P; Taal, M; Tonkin-Crine, S (Elsevier, 2017)
Background Chronic kidney disease (CKD) is often asymptomatic at first diagnosis and awareness of CKD is low among the general population. Thus, individuals who are unexpectedly identified to have CKD may struggle to adjust to living with this diagnosis. This study aims to synthesize qualitative research exploring patients’ views/experiences of the diagnosis of CKD and how they adjust to it. Study design Systematic review and meta-ethnography Setting and Population Adult patients with CKD stage 1-5 Search Strategy & Sources MEDLINE, PsycINFO, CINAHL, EMBASE and Web of Science were searched from the earliest date available to November 2015. Qualitative studies were selected that explored patients’ views and experiences of a CKD diagnosis and how they adjust to it. Analytical Approach Meta-ethnography was adopted to synthesize the findings. Results Ten studies involving 596 patients with CKD from secondary care settings were included. Seven key themes were identified: 1) a challenging diagnosis 2) diverse beliefs about causation 3) anticipated concerns about progression 4) delaying disease progression 5) unmet informational needs 6) psychosocial impact of CKD 7) adjustment to life with CKD. Limitations The review is limited to the views and experiences of participants in the included studies which were mostly conducted in high income countries. Papers not written in English were excluded. The transferability of the findings to other populations may be limited. Conclusions This synthesis highlighted variation in patients’ understanding of CKD, an overall lack of information on the trajectory of CKD and a need for psychosocial support especially in later stages to help patients adjust to living with CKD. Future research that acknowledges CKD as a condition with diverse complicating morbidities and that explores how patients’ information and psychosocial needs vary according to severity and co-morbid conditions would be beneficial. This will support delivery of comprehensible, timely and targeted information about CKD and practical advice about recommended lifestyles changes to manage symptoms and reduce risk of future complicating illness.